FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN KOMUNIKASI TERAPEUTIK BIDAN PUSKESMAS DALAM MEMBERIKAN PELAYANAN KESEHATAN DI PUSKESMAS KOTA SEMARANG TAHUN 2016 Factors Correlated With Therapeutic Communication Of Midwife In Community Health Centre In Giving Heal - Dinda Permatasari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Midwife is a health workers which is included in nursing and has an authority to give midwifery directions, such as in communication, information and education (known as therapeutic). Therapeutic communication is obliged to be done by midwife on behalf resurrection. This research aims to analyze the correlation between several factors with therapeutic communication of midwife in community health centre in giving health service in community health centre Semarang. This research is conducted in Observational Analytic way and uses Cross Sectional Study. Population of the research are 96 midwifes; using 40 samples. The analysis comprises of univariat and bivariat descriptive (crosstab). Bivariat analytic uses Chi Square Test (Pearson, Fisher Exact Test) (α=5%).Univariat test shows respondents percentage are equal for all three major matters, included: young adult (50%) and mature adult (50%), new midwife (50%) and incumbent midwife (50%), good working regulation (50%) and bad working regulation (50%). Most of respondents are coming from bachelor program (97,5%), less acknowledged (55%), good trust (87,5%), good manner (70%), good external (coworker and manager) encouragement (70%), and good therapeutic communication (55%). Bivariat analysis shows correlation between knowledge (p= 0,048), external encouragement (p= 0,002) with therapeutic communication of midwife in giving health care. It is suggested that Health Department of Semarang arise awareness of therapeutic communication. Moreover for community health centre, giving socialization and periodic monitoring.